When Services Fail: Mapping Consumer Protection and Ethical Vulnerability Through Bibliographic Coupling and Co-Word Analysis - Ari Irawan; Taufiq Ismail; April Kim Lalisan (Har Press Indonesia, 2026)
In an era where service breakdowns are increasingly visible and digitally amplified, understanding how firms manage consumer protection, ethical risk, and post-failure recovery has become a critical area of inquiry. Service failures threaten customer trust and satisfaction and expose systemic vulnerabilities in ethical service delivery and complaint resolution. This study aims to map the intellectual and conceptual landscape of research at the intersection of service failure, consumer protection, and ethical vulnerability. Using a data-driven bibliometric approach, it seeks to identify thematic clusters, evolving discourse patterns, and knowledge gaps. A bibliometric analysis was conducted on 677 peer-reviewed journal articles from the Scopus database, published between 2005 and 2025. Two complementary techniques were employed: (1) bibliographic coupling, to identify intellectual linkages among recent publications, and (2) co-word analysis, to map the conceptual structure of recurring themes. The dataset was processed and visualized using VOSviewer software. The bibliographic coupling analysis revealed five thematic clusters, ranging from emotional and tangible strategies in service recovery to customer retaliation and systemic value co-creation/destruction. Co-word analysis identified four thematic clusters: (1) service failure and social media-driven recovery strategies, (2) justice and emotional mechanisms of satisfaction and loyalty, (3) trust, human-centered design, and decision-making in digital service environments, and (4) complaint behavior and service quality in post-recovery evaluation. Across both analyses, concepts such as fairness, emotional regulation, trust, and digital transparency emerged as central constructs linking service ethics with customer experience. The findings reveal a paradigmatic shift in service recovery scholarship from isolated transactional models to emotionally intelligent, culturally contextualized, and digitally networked frameworks. Service failure is increasingly understood as an operational breakdown and an ethical flashpoint, implicating fairness, transparency, and consumer dignity. The study offers a structured knowledge map for future research and managerial innovation at the nexus of ethics, service design, and consumer protection.